PENGARUH KOMITMEN ORGANISASI, DISIPLIN KERJA, DAN SELF EFFICACY TERHADAP KINERJA KARYAWAN PADA PT. TIARA INDAH ABADI CABANG GUNUNG AGUNG DENPASAR - I Kadek Sastra Dwipa; Anak Agung Dwi Widyani; Ni Putu Ayu Sintya Saraswati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
The purpose of this study was to examine and analyze the effect of organizational commitment, work discipline, and self-efficacy on employee performance. To achieve organizational goals, it takes commitment from every employee to the company. In addition to commitment, an employee who does not have work discipline will find it difficult for the organization to achieve its goals. Then the presence of self-efficacy in the individual will lead to confidence in his ability to complete the work given. This research was conducted at PT. Tiara Indah Abadi Gunung Agung Branch, which is located at Jln. Mount Agung No. 125 Denpasar. The sample in this study were all employees, amounting to 36 employees. The sampling technique used was the saturated sample method. The data analysis technique used is multiple linear regression analysis. The results showed that partially organizational commitment, work discipline and self-efficacy had a positive and significant effect on employee performance.